Prognostic value of sST2 in heart failure patients with diabetes. (14th October 2021) - Castiglione, V; Chiriaco', M; Aimo, A; Januzzi, J; Richards, A.M; Lam, C.S.P; Latini, R; Anand, I.S; Ueland, T; Brunner-La Rocca, H.P; Bayes-Genis, A; De Boer, R.A; et al.
Abstract: Background: Soluble suppression of tumorigenesis-2 (sST2) is released in response to inflammation and vascular injury, and holds prognostic value in heart failure (HF). Type 2 diabetes (T2D) is characterized by a pro-inflammatory status and is highly prevalent among HF patients, with adverse impact on outcomes. The clinical value of sST2 in HF patients with T2D has never been characterized. Purpose: We aimed to assess sST2 clinical correlates and prognostic value in HF patients with T2D. Methods: Individual data of 3476 patients with stable chronic HF from 5 cohorts from the BIOS (Biomarkers In Heart Failure Outpatient Study) dataset were analysed, with available N-terminal fraction of pro-B-type natriuretic peptide (NT-proBNP), high-sensitivity troponin T (hs-TnT), and sST2 levels. Results: Mean age was 65±12 years (75% males). T2D was present in 1386 patients (40%), who had higher body mass index (BMI, 27 [24–30] vs. 26 [23–29] kg/m 2, p<0.001), lower estimated glomerular filtration rate (eGFR, 56±22 vs. 60±19 mL/min/1, 73 m 2, p<0.001), higher sST2 (33 [24–47] vs. 27 [20–40] ng/mL, p<0.001), NT-proBNP (1735 [742–3963] vs. 1450 [514–3299] ng/L, p<0.001), hs-TnT (28 [16.2–51.5] vs. 17 [9–31] ng/L, p<0.001) and high-sensitivity C-reactive protein (hs-CRP, 6 [2–11] vs. 4. [2–9] mg/L, p=0.003) (Figure). Differences between sST2 levels in patients with or without T2D were influenced by hs-CRP (p for interaction=0.010) and hs-TnT (p=0.031), but not by NT-proBNP and eGFR. At multivariate linear regression analysis, NT-proBNP, hs-TnT and hs-CRP were independently associated with sST2 levels in both T2D and non-T2D patients. Compared with patients without T2D, those with T2D showed higher 1-year all-cause mortality (12% vs. 10%, p=0.034), cardiovascular mortality (9% vs. 7%, p=0.011), and HF hospitalization rate (22% vs. 12%, p<0.001). In a prognostic model including age, sex, eGFR, ischemic vs- non-ischemic aetiology, left ventricular ejection fraction class, New York Heart Association class, NT-proBNP, hs-TnT, and hs-CRP, sST2 retained independent prognostic value in both patients with or without T2D for 1-year all-cause and cardiovascular mortality, and 1-year HF hospitalization, with higher optimal cut-offs for mortality prediction in T2D vs. non-T2D (39 and 45 vs. 29 and 29 ng/mL respectively for 1-year all-cause and cardiovascular mortality). Conclusions: sST2 is higher in HF patients with T2D and likely linked to a pro-inflammatory status. sST2 maintains its prognostic value both in diabetic and non-diabetic HF patients, independently of NT-proBNP, hs-TnT and hs-CRP. Funding Acknowledgement: Type of funding sources: None.